AUTOMATED DESIGN OF OPTICAL SYSTEMS OF FAST ASPHERICAL LENSES FOR LWIR SPECTRUM - YATSENKO, ANDRIY; SOKURENKO, VYACHESLAV (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In this research, a numerical technique has been experimentally applied for developing extremely fast optical lens systems with a fixed focal length for long-wave infrared range (LWIR) providing the high image quality. In particular, the automated procedure utilizing a modified version of a modern stochastic global optimization algorithm was examined during generating new optical systems of fast infrared lenses. In this paper, the aberration synthesis was done for a few 4-lens optical systems with the effective focal length of 50 mm, a F-number of 0.65 to 1, and angular field of view 16° and 25°. These optical systems are indented to be applied in the long wave infrared spectrum with microbolometer image sensors with a diagonal of the sensitive area equal to 14 mm and 22 mm. The numerical simulations of the optical design process have indicated that the applied global optimization algorithm needs a serious computational time interval when a total number of optimization variables approximately equals to 50. Particularly, when using a personal computer with the Intel Core i9 processor operating in multi-threaded mode and when optimizing the modulation transfer function values (that requires multiple fast Fourier transforms), the optical design process may take 10 hours or more. In all designed infrared lenses, the residual value of the relative distortion was less than 1%, while the polychromatic modulation transfer function values at the spatial frequency of 40 lines/mm exceeded 40% for the whole field of view. The presented results confirmed the practical effectiveness of the numerical technique to generate automatically well-corrected both onto monochromatic and chromatic aberrations fast aspheric LWIR lenses utilizing germanium and zinc selenide.
Keywords: aspherical lens; long-wave infrared range (LWIR); automated design; image quality; germanium; zinc selenide